Tropical Medicinal Plant Extracts Against Rice Weevil, Sitophilus oryzae L. - Khani, Mousa; Muhamad Awang, Rita; Omar, Dzolkhifli; Rahmani, Mawardi; Rezazadeh, Shamsali (Academic Journals, 2010)
Rice weevil, Sitophilus oryzae L. is one of the major pests of stored commodities, the adult weevils feed on rice and the females lay eggs inside rice kernels. In the study chemical composition of extracts from black pepper, Piper nigrum L. and physic nut, Jatropha curcas L. were tested against this pest, under laboratory conditions. The chemical compositions of the extracts were identified by gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). The major extracted components of P. nigrum were piperine (74.34%) and caryophyllene (18.53%), and for J. curcas were oleic acid (40.67%), linoleic acid (34.17%) and palmitic acid (18.03%). The mortality of adults increased with increasing concentration of extracts from 2 to 10 μl/g of rice and exposure time from 24 to 72 h. The petroleum ether (LC50=1.61 μl/g) and chloroform extracts (LC50=1.70 μl/g) of P. nigrum showed higher mortality rate compared to petroleum ether extracts (LC50=6.82 μl/g) of J. curcas with 99.56, 93.56 and 66.00% mortality, respectively. The P. nigrum extracts (92.0%) were significantly repelled S. oryzae compared to J. curcas extracts (69.6%). Petroleum ether and chloroform extracts of P. nigrum and petroleum ether extract of J. curcas extracts also showed strong antifeedant and opposed to progeny production. Furthermore, F1 adults were suppressed at the lowest concentration (2 μl/g) and no F1 was produced in all treatments. The results of this study show that P. nigrum and J. curcas extracts were able to protect stored grain.